A Comprehensive Bibliometric Analysis of fNIRS and fMRI Technology in Neuromarketing - Ahmed Alsharif; Nor Zafir Md. Salleh; Lina Pilelienė (Scientific Annals of Economics and Business, 2023)
The aim of this study is to perform a comprehensive bibliometric analysis of functional near-infrared spectroscopy (fNIRS) and functional magnetic resonance imaging (fMRI) tools. To achieve this aim, we adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol and bibliometric analysis (VOSviewer) for extracting the relevant papers (articles and reviews) from the Scopus database between 2002 and 2022. A total of 86 papers were included in the analysis. The results showed an increasing trend in publications over the years—the top countries in terms of publication outcome were the United States, Germany, Spain, and Australia. The analysis also identified the most influential authors and institutions in the field. In addition, we analyzed the most frequently cited articles, journals, and keywords related to fNIRS and fMRI tools. This bibliometric analysis provides insights into the current state of research on fNIRS and fMRI tools. It also provides insights into the direction of future research in this field. In this study, we will provide general insights and details about current trends in neuromarketing research using fNIRS and fMRI.